Financial Development and Energy Consumption Nexus in 32 Belt and Road Economies - Janpolat, Kudaybergenov; Odilova, Shoirahon; Nodira, Abdusalomova; Salahodjaev, Raufhon; Khachaturov, Anastas (International Journal of Energy Economics and Policy, 2021)
Current study sheds the light on the financial development-energy nexus in 32 Belt and Road economies during 2000-2015. Financial development is proxied by domestic credit to private sector. We first examine the order of integration by employing five different panel unit-root tests. Further, we confirm long-term relationship between the variables by running Pedroni and Kao panel cointegration tests. Fully Modified Ordinary Least Squares (FMOLS) regression reveal positive long-term relationship between financial development and energy use. Results of Dumitrescu-Hurlin panel causality test fail to reveal causal relationship between financial development and energy in our sample. Keywords: energy consumption, financial development, Belt and Road countries JEL Classifications: G2, O4 DOI: https://doi.org/10.32479/ijeep.10862